PRELIMINARY EFFECTS OF INTEGRATED RELAXATION AUDIO (ARTIKU) ON REST QUALITY IN PALLIATIVE PATIENTS: A QUASI-EXPERIMENTAL STUDY - Sri Djuwitaningsih; Yuli Mulyanti; Syafdewiyani Syafdewiyani; Deswani Deswani; Indra Gunawan (Poltekkes Kemenkes Jakarta III, 2026)
Patients with terminal illnesses frequently struggle with anxiety, chronic pain, and sleep disorders, which can seriously lower their quality of life. ARTIKU (Integrated Relaxation Audio) is a non-pharmacological approach to innovative integrated audio relaxation therapy that combines murotal, guided imagery, and the five-finger relaxation technique. This study aims to explore the preliminary effects of ARTIKU therapy on rest quality in palliative care patients. This study used a quasi-experimental design with a one-group pretest–posttest. As many as 34 palliative patients were selected using purposive sampling. The ARTIKU music therapy was administered for three consecutive days. Measurements were taken pre-post intervention using the ARTIKU questionnaire, which measured pain level, sleep duration, and anxiety. A paired sample t-test was used to analyze the data. The median values for anxiety and pain levels decreased significantly, from 2.00 to 1.00 (Z = -5.11; p < 0.001) and from 5.00 to 2.50 (Z = -4.49; p < 0.001), respectively. On the other hand, patients' sleep duration increased significantly from 4.00 to 5.50 hours (Z = -4.95; p < 0.001). The ARTIKU therapy intervention is highly effective in alleviating pain and anxiety, as well as enhancing sleep duration among palliative patients. ARTIKU therapy demonstrates preliminary effects in improving rest quality among palliative patients, showing significant improvements in pain, sleep duration, and anxiety. These findings suggest that ARTIKU has potential as a non-pharmacological intervention and warrant further investigation through randomized controlled trials with larger sample sizes and longer intervention duration to confirm its effectiveness.